Turtles as Hopeful Monsters : Origins and Evolution - Rieppel, Olivier (Book collections on Project MUSE., 2017)
Where do turtles hail from' Why and how did they acquire shells' These questions have spurred heated debate and intense research for more than two hundred years. Brilliantly weaving evidence from the latest paleontological discoveries with an accessible, incisive look at different theories of biological evolution and their proponents, Turtles as Hopeful Monsters tells the fascinating evolutionary story of the shelled reptiles. Paleontologist Olivier Rieppel traces the evolution of turtles from over 220 million years ago, examining closely the relationship of turtles to other reptiles and charting the development of the shell. Turtle issues fuel a debate between proponents of gradual evolutionary change and authors favoring change through bursts and leaps of macromutation. The first book-length popular history of its type, this indispensable resource is an engaging read for all those fascinated by this ubiquitous and uniquely shaped reptile.